Study On Sports Socialization Among University Students (GYMNASIUM, 2021)
It is well known that participation in various physical sports activities contributes to the physical, psychological and emotional development of students, as well as their ability to socialize. A large part of students who come at university from other cities and have an increased need to socialize and build new groups of friends, especially in the first years of study, can use sports activities as a method of socialization. The purpose of this paper is to analyze how university students socialize through physical activities and sports. Using the method of quantitative research, the technique of administering questionnaires through sociological survey, we conducted a study with students from the Technical University of Cluj-Napoca, in the 2019-2020 academic year, with 594 of participants. The results of the study can help young people to use participation in various physical sports activities as an opportunity to socialize, meet other people and make new friends.
Keywords: physical activity, socialization, sport, student population.